Self-employment in crafts-an option for the disabled hearing impaired (2001)
This study examined self-employment as an option for the disabled hearing impaired using the exploratory design. Of the 80 respondents who took part in the survey 19(23.8%) were teachers of the hearing impaired, 19(23.8%) were hearing impaired employees, 37 (46.2%) were hearing impaired apprentices and 5 (6.2%) were self employed hearing impaired persons. Four sets of self-administered questionnaire were used for data collection from the different groups of respondents. Findings showed that the hearing impaired could be self-employed, cope with new demands and developments involved in self employment. Good educational background and period of apprenticeship were found to be prerequisites for self employment. Communication was reported by 61.3% of respondents to be a barrier to self-employment. The implications of these education and rehabilitation of the healing impaired are discussed.